A Note on General Radicals of Paragraded Ringsa Note on General Radicals of Paragraded Rings - Ilić-Georgijević, Emil; Vuković, Mirjana (Sarajevo Journal of Mathematics, 2024)
We discuss the general theory of radicals of paragraded rings, establish that the ADS-Theorem holds, and characterize paragraded normal radicals. It is known that any special radical of a ring can be described by the appropriate class of modules over that ring. In this note we show that all special paragraded radicals of paragraded rings can be described by the appropriate class of their paragraded modules. * This paper was presented at the International Scientific Conference Graded structures in algebra and their applications, dedicated to the memory of Prof. Marc Krasner, IUCDubrovnik, Croatia, September, 22-24, 2016.